Eâ€“Business: Teknologi dan Peluang Bisnis di Indonesia - Widhianto, Chandra Wibowo (Journal the Winners: Economics, Business, Management, and Information System Journal, 2002)
Information technology offers creativity and business inovation rapidly and easily. A business must see the new opportunity. Microsoft give solution that will â€œspoilâ€ business man in implementation, management, and the exploitation of the information technology maximally. The information technology is cheap and easy to applied now.